From bad to worse: How Russia-Ukraine war-related export restrictions exacerbate global food insecurity - Glauber, Joseph W.; Laborde Debucquet, David; Mamun, Abdullah (International Food Policy Research Institute, 2023)
Global turmoil and supply shocks can increase a country’s vulnerability to food shortages. In the past, countries have often resorted to restrictive trade policies to address food supply disruptions. The Ukraine-Russia crisis is no exception; a number of countries have imposed export restrictions in various forms. With food prices already high due to COVID-19-related supply chain disruptions and drought-reduced yields in 2021, Russia’s invasion came at a bad time for global food markets. Russia and Ukraine alone account for 12% of total calories traded. As the war continues, there is a growing likelihood that food shortages, particularly of grains and vegetable oils, will become acute, leading more countries to turn to restrictions on trade.